Environmental literacy profile in Bantul, Special Region of Yogyakarta - Wardatul Uyun; S. Suhartini (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Environmental issues are occurring more frequently, both due to natural causes and human activities. If left unchecked, human activities can worsen environmental conditions. Bantul Regency in the Special Region of Yogyakarta, Indonesia, is one of the regions grappling with this issue, primarily due to waste management and industrial activities. Environmental issues are related to environmental literacy. The lack of education, awareness, and knowledge in society can degrade environmental quality. Environmental literacy plays an important role in enhancing knowledge as well as changing the attitudes and behaviors of society towards the environment. Therefore, it is important to instill environmental literacy in individuals to improve our attitudes towards the environment. This study aims to provide an overview of students's environmental literacy in Bantul Regency. The research uses a survey method conducted in Bantul Regency from September to November 2023. The population of this study includes all 10th-grade students from public high schools in Bantul Regency. The sample consists of 300 10th-grade students from public high schools in the sub-districts of Bantul, Banguntapan, Sewon, Jetis, Piyungan, Imogiri, Pajangan, Srandakan, Sedayu, and Dlingo. The study's results show that the environmental literacy profile of 10th-grade students in Bantul Regency falls into the "average" category, with a percentage score of 65.96%. The highest score in the competency domain is found in Bantul City (81.90%) and falls into the "good" category, while the lowest score is in Dlingo Sub-district (60.93%), categorized as "average" The highest score in the affective domain is in Dlingo Sub-district (70.25%), categorized as "average" while the lowest score is in Jetis Sub-district (66.67%), also categorized as "average." The highest score in the behavior domain is found in Imogiri Sub-district (64.91%), categorized as "average" while the lowest score is in Srandakan Sub-district (55.30%), categorized as "low."